Reforming Fiscal Governance in the European Union - Andrle, Michal (Staff Discussion Notes; Staff Discussion Notes, 2015)
Successive reforms have brought many positive elements to the European Union's fiscal framework. But they have also increased its complexity. The current system involves an intricate set of fiscal constraints, which hampers effective monitoring and public communication. Compliance has also been weak. This note discusses medium-term reform options to simplify the framework and improve compliance. Based on model simulations and practical considerations, it argues for moving to a two-pillar approach, with a single fiscal anchor (public debt-to-GDP) and a single operational target (an expenditure growth rule, possibly with an explicit debt correction mechanism) linked to the anchor.